Avaliação fotocatalítica de niobatos lamelares: influência dos métodos de síntese, aspectos teóricos e experimentais - Souza, Juliana Kelly Dionízio de (2018)
The use of semiconductors as photocatalysts is a promising strategy in the treatment of organic pollutants. In this sense, the photocatalytic performance of lamellar potassium niobates and their protonated forms were tested for the degradation of the model dye Remazol Yelow Gold (RNL). The niobates (KNb3O8 and K4Nb6O17) were prepared by the polymeric precursor (PP) and solid state (SS) methods. The protonated forms HNb3O8.H2O and K4-xHxNb6O17, obtained by the PP method, were prepared via a ion exchange reaction using a HNO3 solution. The materials were characterized by X-ray di?raction (XDR), infrared (IR), Raman, ultraviolet visible (UV-vis), scanning electron microscopy (SEM), surface area (BET) and photoluminescence (PL). Theoretical Computational calculation were performed (DFT) to de?ne the structural and vibrational aspects of niobates in the potassium form. Their structures were characterized at long, medium and short range are in accordance with those in the literature. The theoretical studies of octahedron distortions showed that KNb3O8 has two types of distortion, where as K4Nb6O17 has four types. The octahedron with the largest distortion degree for K4Nb6O17 has a short Nb - O bond (high covalent character) and another much elongated one (with a transient character between the covalent and the ionic). It is observed that niobates in the potassium form have better photocatalytic performances when compared to either their protaned forms or P25. Studies to elucidate the mechanism of discoloration for the potassium niobates used suppressors of •OH, O•- 2 radicals, e- and h+. The results show that the mechanism of photocatalysis is indirect, that is, by the formation of •OH radicals . For KNb3O8 the formation of •OH radicals a high contribution of photogenerated e- in the conduction band is observed, whereas, both e- and h+ are responsible for the formation of these radicals for K4Nb6O17. For the RNL discoloration reaction using KNb3O8 reactional parameters were studied, such as pH, initial concentration of dye (C0), photocatalyst quantity and calcination temperature. Three reuse cycles were analyzed for potassium niobates, which indicated little loss of catalytic activity.